Apostolate from the Point of View of the II Vatican Council - Balter, Lucjan (Studia Theologica Varsaviensia, 2020)
e panorama of the Council’s thinking about the universal apostolate, sketched out in brief, is increasingly becoming the property of the people of God: it permeates the minds and hearts, is reflected in the practice of daily life, in the initiatives and apostolic undertakings taken, in the way of thinking and acting. It would be difficult to say, of course, what the actual state of current apostolic activity in the Church is, if we had separate sociological studies. Nevertheless, it should be stated and strongly emphasised that the pioneering suggestions of Vincenzo Palottis, enriched by the experience and reflections of future generations, the contributions of Newman, Perrone and others, deepened and adapted according to the demands of the times by the Second Vatican Council, have already become a lasting heritage and property of the whole people of God, who are becoming increasingly more aware that they are by their very nature, and therefore must be in practice, a people who are eminently apostolic.